Development of Interactive Video Learning Media Using Canva Application in Social and Natural Sciences (IPAS) Subject for Grade V at SDN 10 Koto Baru - M. Anggrayni; Dwi Novri Asmara; Rahmi Septiara (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study is motivated by the lack of student interest and focus on the learning material delivered by the teacher. During the learning process, the teacher only explained and provided examples, which made it difficult for students to develop their thinking patterns and express their ideas comprehensively. The purpose of this research is to explore the development of interactive video learning media using the Canva application for the IPAS subject in Grade V at SDN 10 Koto Baru. This research is a type of Research and Development (R&D) using the ADDIE development model. Based on validation results, the language aspect scored 86% (very valid), material validation 94% (very valid), media validation 96% (very valid), test item validation 73% (valid), and module validation 95% (very valid). The practicality level of the interactive video learning media, as assessed by teachers, reached an average score of 98% (very practical), while students rated it at 97.04% (very practical). The effectiveness of the interactive video learning media, based on student learning test results, reached an average of 88.88%. Therefore, it can be concluded that the interactive video learning media using the Canva application for the IPAS subject in Grade V of elementary school is valid, practical, and effective.